THERAPEUTIC COMMUNICATION AND 'KNOW, CHECK, ASK' EFFECTS ON FAMILY ANXIETY - Apriliyanti, Fitria; Pebru Nurlaily, Ari; Murharyati, Atiek (Journal of Vocational Nursing, 2024)
Introduction: Emergency treatment often causes anxiety and fear for patients and their families. One way to reduce anxiety is through therapeutic communication. In commemoration of World Patient Safety Day (WPSD) on September 17, 2022, WHO and the Ministry of Health announced slogans about before providing and receiving drugs namely Know (understand drugs and their side effects), Check (check according to the 5 correct drugs), and Ask (ask for information that is not understood). The purpose of this research is to determine the relationship between therapeutic communication and the application of the slogan Know, Check, and Ask before drug administration on the anxiety level of the patient's family in the emergency room of PKU Muhammadiyah Sukoharjo Hospital. Methods: The type of research was quantitative with a descriptive Corelative design and a cross-sectional approach. The sampling used the Quota Sampling technique based on Yount's formula (1999) 5% of the population with 57 sample respondents. The research was conducted in June 2023. Results: The Spearman Rank test analysis obtained a p-value = 0.000 (<α = 0.05), meaning that there is a relationship between therapeutic communication and the implementation of the slogan of Know, Check, and Ask before administering medication to the anxiety level of the patient's family in the IGD room of PKU Muhammadiyah Sukoharjo Hospital. Conclusions: The application of therapeutic communication with the slogan Know, Check, and Ask before drug administration should be maintained properly because it is related to the anxiety level of the patient's family.